HANDOUT BERBASIS GUIDED NOTE TAKING PADA MATERI KOLOID - Nurul Alfi Syahra; M. Nasir; Sri Winarni (Majelis Pendidikan Aceh, 2021)
The static of students in making learning notes, especially on rote material is one of the triggers for the low learning outcomes of students. The objectives of the study were to: (1) analyze the feasibility of HGNT on colloidal material, (2) describe the responses of teachers and students to HGNT on colloidal material. The research method used is Research and Development with a 4-D model. Includes four stages, namely: (1) define (2) design; (3) develop and; (4) disseminate. But in the development of HGNT, it is only carried out until the third stage. The research was conducted at MAN 3 Banda Aceh with research subjects 27 students of class XII MIA 1 and chemistry teachers who are members of the MGMP chemistry forum. The developed handout has a very decent assessment criteria with a percentage of 90%. The results of the teacher's responses are in the very good category with a percentage of 82.5% and student responses of 73% which are in the good and practical category.